Gênero textual autobiografia em aulas de língua portuguesa na EJA : uma perspectiva de aprendizagem na terceira idade - Volponi, Margaret de Lourdes (2015)
In Brazilian public education there is a major gap related to teaching resources: Youth and Adults Education is forgotten and undervalued by the public policies, and there are no traces of teaching changes including appropriate and specific resources aimed at elderly education. This shows a great lack of exclusive tools for the teaching and learning regarding these groups. Bearing in mind the statement above, this research develops a proposal for the production of teaching resources aimed at Portuguese language teachers, so they can use the text genre autobiography with elderly students of the Youth and Adult Education (EJA, from now on). In order to support the reflections for this research, it is based mainly on the review of its specific literature. Firstly, it was based in three main points: 1 -the research was made up of appropriate selected texts analysis, which provided the theoretical approach, in which storytelling, reading and writing are based on theories which address enunciation, dialogism and the interaction through language, according to Bakhtin's view (1992/2003); 2- the proposal of the State Bureau of Education (1999) is bound to the PCNs - 2008 (Brazilian Curricular Parameters); and 3- the research is based on texts of renowned authors such as Geraldi (2003), Bakhtin (1992/2003) and Brandão (2003). At a second moment, the teaching resources used at a State Center of Basic Education for Youth and Adults (CEEBJA) in the city of Sarandi, with students of basic education - second stage, are analyzed and, following, a teaching sequence was developed as a guiding strategy for teaching practices to attain a language teaching more suitable to the social dynamics of EJA. The development of this research aims at providing the Portuguese language teachers tools to work the genre autobiography, as well as creating tools for elderly students to write down their own history. This way, it contributes for the effectiveness of the learning process to thisgroup.